外资运用与河北经济增长问题研究 = The impact of foreign capital utilization on Hebei's economic growth - 马文清 Ma, Wenqing (2008)
Due to relatively little study on the contribution of foreign capitals on Hebei's economy, the aim of this thesis is to analyse empirically the role of foreign capitals on the economic development in Hebei province.